Antara Mengelabuhi atau Mencari Untung: Adakah Fraud Accounting dibalik Permainan Angka diatas Kertas? - Rafles Ginting; Teressa Lang; Sara Sara; Novita Novita; Khristina Yunita (Magister Akuntansi Universitas Pancasila, 2023)
The practice of fraud is certainly not a new phenomenon in people's lives, this practice is like an epidemic that spreads to various circles and levels. The practice of fraud plunges a person into the abyss of loss which will certainly have an impact on prosperity and the economy whose consequences can be felt by many people. Enriching yourself is the goal of this practice, because there is a feeling of dissatisfaction with what you already have. Fraudulent practices can be found in all agencies and organizations as well as other businesses, one of which is the photocopy shop business. Methods of collecting and analyzing data in this study with interviews, observation, and documentation. The results of this study indicate that there are fraudulent practices in the photocopying business and that the average customer who requests blank notes comes from all walks of life. In this study it was found that the practice of fraud occurred in the photocopy shop business by manipulating blank notes using various reasons, such as cigarette money, transportation money or other personal interests. However, there are also photocopy shop businesses that don't want to do this because they think it can hurt the store's image.